The law of God : exploring God and civilization - Vos, Pieter, 1970- (Studies in Reformed Theology, 2014)
In today's society, a positive relation between 'God' and 'civilization' is by no means self-evident. Religious believers who want to live their lives in accordance with 'the law of God' are often considered a threat to civilization. To many, monotheistic religion is inherently repressive and violent. The central aim of this volume is to think of both God and civilization in a more open, space-giving way. God is seen as the One who prevents man from making an absolute claim for a relative reality, including one's religion and culture. The multifaceted relations between God and civilization are explored from systematic-theological, missiological, philosophical and ethical perspectives.